IMPLEMENTATION OF UNDERSTANDING OF PAI VALUES IN NATURE CONSERVATION TO BUILD ENVIRONMENTAL AWARENESS IN EDUCATIONAL INSTITUTIONS IN BANTEN PROVINCE - Saebah, Saepul Bahri (TA`DIBUNA, 2025)
Background: The issue of environmental degradation has become a major challenge around the world, as human-induced damage to ecosystems continues to worsen. Pollution, deforestation, species depletion, and weather changes are signs that environmental awareness in society is still low. This research aims: The purpose of this study is to understand the values in Islamic Religious Education (PAI) that relate to protecting nature and the environment as a religious and social responsibility. To find the ways in which Islamic Religious Education values are applied in the effort to protect the environment by various educational institutions in Banten Province. Creating strategic suggestions for developing an environmental education model based on Islamic values, so that it can be well integrated into the education system at the local and national levels. The method applied in this study is naturalistic qualitative, which focuses on naturally occurring circumstances in educational institutions (schools). The findings of this study show that Islamic values related to nature protection, such as tawhid, amanah, rahmatan lil 'alamin, and khilafah, have been incorporated into Islamic Religious Education (PAI) materials, especially on themes that discuss the relationship between humans and nature. In this case, PAI teachers function as drivers and supporters in instilling Islamic values related to the environment.